Torsional Strengthening of RC Beams with Openings Using Hybrid SHCC–Glass Fiber Mesh Composites - Ahmed Hamoda; Saad A. Yehia; Mizan Ahmed; Aref A. Abadel; Khaled Sennah; Vipulkumar Ishvarbhai Patel; Hussam Alghamdi (Buildings)
This study investigates the effectiveness of strain-hardening cementitious composites (SHCC) reinforced with glass fiber (GF) mesh in enhancing the torsional behavior of reinforced concrete (RC) beams with circular openings. Eight full-scale RC beams were tested under pure torsion, including two control beams and six strengthened beams with varying configurations of horizontal, vertical, and combined SHCC-GF mesh retrofitting. The experimental program evaluated the influence of single- and double-layer GF mesh reinforcement on torsional capacity, crack propagation, stiffness, and energy absorption. The results demonstrated that the presence of an opening reduced the ultimate torsional capacity by 29%, elastic stiffness by 48%, and energy absorption by 64% compared to the solid control beam. Strengthening with horizontal SHCC strips restored 21–35% of the lost capacity, while vertical strips performed even better, achieving 44–61% improvement. The combined horizontal–vertical configuration with a double-layer GF mesh proved the most effective, increasing ultimate load by 91% compared to the unstrengthened beam with an opening. Finite element models (FEM) are developed using ABAQUS to simulate the performance of the tested beams.